Performance of cashew types under Bhubaneswar condition - Sethi, K.; Mohapatra, K.C.; Tripathy, P.; Dash, P.C. (Journal of Plantation Crops, 2015)
An experiment was conducted at the Cashew Research Station of Orissa University of Agriculture and Technology, Bhubaneswar, Odisha, India during 1994 to 2011 to identify the cashew types for commercial cultivation under Odisha condition. Evaluation of the 13 cashew types over fourteen years revealed significant variations for nut yield among the types. The result indicated a wide range of variation for different parameters under study. The maximum average number of nuts panicle-1 was recorded in H 303 (4.19). Highest weight (g) of nut as well as apple was observed in H 367 (9.7 and 92.7). All the cashew types under study exhibited shelling percentage more than 28 but maximum kernel recovery was observed in H 255 (31.7). BPP 30/1 and M44/3 were the early flowering types that recorded panicle initiation during 4th week of November, whereas NRCC Sel.-1 and H 255 were late flowering types that flowered during first week of January. The flowering period ended first in M 15/4 (1st week February) while it was during 3rd week of March in H 255 and BPP 3/28. Maximum flowering duration was observed in BPP 30/1 (96 days) and minimum in NRCC Sel.-2 (59 days). The cumulative nut yield (kg plant-1) at 14th harvest was observed in H 303 (106.8) followed by NRCC Sel.-2 (100.0), H 68 (93.1) and lowest in M 15/4 (37.5).